TINDAK TUTUR ILOKUSI PADA MEDIA ONLINE MOJOK.CO - Rifda Nabila; Imam Baehaqie (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the types of illocutional speech acts, functions, and pragmatic implications in essay articles on Mojok.co for the period September-November 2025. In this study, a pragmatic approach (as a theoretical approach) and a qualitative descriptive approach (as a methodological approach) are used. Data in the form of speech quotes selected from Mojok.co essays were collected using the free listening method and note-taking techniques to assess proficiency. The data were analyzed using a pragmatic matching method based Searle’s illocution classification and Leech’s illocution function. The results of the study show that there are five types of illocution, namely assertive, directive, commissive, expressive, and declaration, as well as four functions, namely competitive, convivive, collaborative, and conflictive. The study concludes that the illocution strategy is used to frame issues, direct readers’ judgment, and strengthen social criticism in digital discourse.